“Bettonan” Contract in Agricultural Management as Poverty Reduction Efforts From Islamic Law Point of View - Suwardi Suwardi; Muhammad Erfan Muktasim Billah (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2022)
The background of this research is the existence of a